2013
DOI: 10.1080/09205063.2013.777228
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility of polymeric nanostructured surfaces

Abstract: Tissue integration is an important property when inducing transplant tolerance, however, the hemocompatibility of the biomaterial surface also plays an important role in the ultimate success of the implant. Therefore, in order to induce transplant tolerance, it is critical to understand the interaction of blood components with the material surfaces. In this study, we have investigated the adsorption of key blood serum proteins, in vitro adhesion and activation of platelets and clotting kinetics of whole blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 62 publications
2
50
0
1
Order By: Relevance
“…One important method in this respect is electrophoresis, and here especially the corresponding 2D and/or Western blot techniques 116. 117 It should be considered that different methods including comparative instrumental analyses of surface bound proteins, e.g., by XPS and biochemical analysis of desorbed proteins in solution, may provide substantially different results 118. This is due to incomplete desorption and/or the limited capability of surface‐based analytical techniques to access porous polymer structures.…”
Section: Methods For the Analysis Of Protein Interactionsmentioning
confidence: 99%
“…One important method in this respect is electrophoresis, and here especially the corresponding 2D and/or Western blot techniques 116. 117 It should be considered that different methods including comparative instrumental analyses of surface bound proteins, e.g., by XPS and biochemical analysis of desorbed proteins in solution, may provide substantially different results 118. This is due to incomplete desorption and/or the limited capability of surface‐based analytical techniques to access porous polymer structures.…”
Section: Methods For the Analysis Of Protein Interactionsmentioning
confidence: 99%
“…Platelet adhesion and activation studies were performed by following a modified procedure reported previously 4042 . In brief, whole blood from the healthy donor was drawn into standard 6 mL vacuum tubes coated with the anti-coagulant, EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…Titanium‐based implants have received a great deal of attention for their biocompatibility with many different tissues in the human body . However, when these implants come in contact with blood, platelet adhesion and activation occur, which may lead to further thrombosis and sometimes failure of these implants . It is well known that blood platelet adhesion and activation can be tailored by tuning the chemistry and texture of surfaces .…”
Section: Contact Angles and Roll‐off Angles Of Human Blood Plasma On mentioning
confidence: 99%